Peran Orang Tua terhadap Penyelenggaraan PAUD Inklusi di TK Nusa Indah - Dwi Astuti, Retno (ACIECE, 2019)
This reserch aims to determine how the role of parents in early childhood inclusion. The studywas conducted using a qualitative approach with case study. Course of a study conducted in TK Nusa Indah with research subjects the role of parents TK Nusa Indah. Methods of data collection using observation, wawacanra, and documentation. Data were analyzed using an interactive model of Miles and Huberman. Results from the study include: the role of parents guardians TK Nusa Indah and parental benefits from the involvement of parents in school activities. The shape of the role of parents in TK Nusa Indah, namely: (1) parenting; (2) parents accompany children in activities fied trip; (3) parents to volunteer in the market's activities; (4) speakers in regular discussion activities; (5) parent and child to make toys from waste project; (6) the parents a guest teacher in the classroom according to the theme; and (7) parents are involved in school committees called POM (association of parents). While the perceived benefits of keteribatan active parents in early childhood inclusion, among others: (1) parents can accompany and stimulate the development of the child; (2) parents will accept, acknowledge, give it a chance, and give appreciation to the achievement of an ordinary child and crew in particular; (3) parents to know the needs, interests and talents of the child; and (4) the parents respect children's rights